High levels of 25-hydroxyvitamin D 3 [25(OH)D 3] and α-tocopherol prevent oxidative stress in rats that consume Thai brown rice - Suwannalert P. (2017)
Oxidative stress has been proposed to play an important role in the progression of chronic diseases. The red color strain of Thai brown rice, a high source of phenolic compounds, may play a crucial role in oxidative stress prevention. In the present study, rats were fed with 0% (Control), 10 and 70% Thai brown rice in the mixed food. The serum malondialdehyde (MDA), ferric reducing antioxidant power (FRAP), storage vitamin D [25(OH)D 3 ] and α-tocopherol were investigated. The mean value of MDA in high and low dose groups was significantly lower than that of the controls in both male and female. FRAP in the high dose males was significantly higher than that in the control. Mean value of MDA and α-tocopherol was inversely related (r = -0.538, p =0.001). Interestingly, serum 25(OH)D 3 of the high dose group was more significant different than that of the controls in both males (p = 0.001) and females (p = 0.005). Moreover, MDA level was strongly inversely related to that of 25(OH)D 3 (r = -0.656, p < 0.001). The results indicated that the rats consuming Thai brown rice possessed low level of oxidative stress marker, MDA, through both radical and non radical defenses. © 2010 Academic Journals.